2023
DOI: 10.3390/molecules28186513
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Analysis of the Mechanism of Astaxanthin Succinate Diester in Reducing Ulcerative Colitis in C57BL/6J Mice Based on Microbiota Informatics

Xing Qiao,
Qun Gao,
Lu Yang
et al.

Abstract: This paper aims to explore the effect and mechanism of water-soluble astaxanthin succinate diester (Asta-SD) on ulcerative colitis (UC) induced by dextran sodium sulfate in zebrafish and C57BL/6J mice. Asta-SD was synthesized with hydrophilic fatty acid succinic anhydride and the hydroxyl groups at the ends of F-Asta were synthesized by esterifying. Through the construction of a zebrafish intestinal inflammation model, it was found that Asta-SD could effectively reduce the levels of ROS and increase the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…Asta-SD decreased the gene expression levels of TNF-α, IL-6, and IL-1β. Furthermore, this study also found that the abundance of Bacteroides, Parabacteroides, and Butyrimionas were positively correlated with the gene expression of IL-6 [162]. These findings suggest the Asta-SD ameliorates inflammation in an animal model of UC via the maintenance of intestinal microbiota homeostasis.…”
Section: Beneficial Effects Of Astaxanthin In Intestinal Inflammationsupporting
confidence: 61%
See 1 more Smart Citation
“…Asta-SD decreased the gene expression levels of TNF-α, IL-6, and IL-1β. Furthermore, this study also found that the abundance of Bacteroides, Parabacteroides, and Butyrimionas were positively correlated with the gene expression of IL-6 [162]. These findings suggest the Asta-SD ameliorates inflammation in an animal model of UC via the maintenance of intestinal microbiota homeostasis.…”
Section: Beneficial Effects Of Astaxanthin In Intestinal Inflammationsupporting
confidence: 61%
“…Ax-Alg was demonstrated to reduce the level of LPS and translocate it from the intestinal lumen to the blood in DSS-induced colitis, suggesting that astaxanthin may attenuate the inflammatory response in colitis by inhibiting LPS expression or translocation [160]. A recent study reported that astaxanthin succinate diester (Asta-SD) counteracted the downward trend of the F/B ratio and reduced the abundance of Bacteroides, Geobacter, Alistipes, Butyrimionas, and Parabacteroides in mice with DSS-induced colitis [162]. Treatment with Asta-SD also promoted the proliferation of beneficial bacteria Anaerotruncus and Lactobacillus.…”
Section: Beneficial Effects Of Astaxanthin In Intestinal Inflammationmentioning
confidence: 99%